Novel Assay Platform to Evaluate Intracellular Killing of Mycobacterium tuberculosis: In Vitro and In Vivo Validation - Horváti, Kata; Fodor, Kinga; Pályi, Bernadett; Henczkó, Judit; Balka, Gyula; Gyulai, Gergő; Kiss, Éva; Biri-Kovács, Beáta; Senoner, Zsuzsanna; Bősze, Szilvia (Frontiers in Immunology, 2021)
One of the main hallmarks of tuberculosis (TB) is the ability of the causative agent to transform into a stage of dormancy and the capability of long persistence in the host phagocytes. It is believed that approximately one-third of the world’s population is latently infected with Mycobacterium tuberculosis (Mtb), and 5-10 % of these individuals can develop clinical manifestations of active TB even decades after the initial infection. In this latent, intracellular form, the bacillus is shielded by an extremely robust cell wall and becomes phenotypically resistant to most antituberculars. Therefore, there is a clear rationale to develop novel compounds or carrier-conjugated constructs of existing drugs that are effective against the intracellular form of the bacilli. In this paper, we describe an experimental road map to define optimal candidates against intracellular Mtb and potential compounds effective in the therapy of latent TB. To validate our approach, Isoniazid, a first-line antitubercular drug was employed, which is active against extracellular Mtb in the sub-micromolar range, but ineffective against the intracellular form of the bacteria. Cationic peptide conjugates of Isoniazid were synthesised and employed to study the host-directed drug delivery. To measure the intracellular killing activity of the compounds, Mtb infected MonoMac-6 human monocytic cells were utilized. We have assessed the antitubercular activity, cytotoxicity, membrane interactions in combination with internalisation efficacy, localisation and penetration ability on interface and tissue-mimicking 3D models. Based on these in vitro data, most active compounds were further evaluated in vivo in a murine model of TB. Intraperitoneal infectious route was employed to induce a course of slowly progressive and systemic disease. The well-being of the animals, monitored by the body weight, allows a prolonged experimental set-up and provides a great opportunity to test the long-term activity of the drug candidates. Having shown the great potency of this simple and suitable experimental design for antimicrobial research, the proposed novel assay platform could be used in the future to develop further innovative and highly effective antituberculars.